Uterotonic Potential of Selected Plants Used by Ugandan Local Communities in the Treatment of Malaria - Katuura, Esther; Kalabika, Enock; Lubega, Aloysius (European Journal of Medicinal Plants, 2018)
Malaria is a major cause of death among pregnant women and children under the age of five in Uganda. It is the leading cause of anemia among pregnant women and low birth weight in infants [1]. Majority of the rural population rely on herbs for treatment of various diseases. The leaf extracts of various plants including Bothlioclines longipes, Vernonia amygdalina, Rhus natalensis and Maesa lanceolata are used to treat various diseases including malaria in Uganda. The local communities prefer herbal preparations from the leaves of the plants. Extracts from the leaves of the plants were proven efficacious against P. falciparum in earlier studies in vitro. This study was carried out to investigate the effect of Diethyl ether and methanol extracts on the contractility of an isolated rabbit uterus and also to quantitatively analyze for iron and zinc in the leaves of these plants. The diethyl ether extracts of V. amygdalina, M. lanceolata and R. natalensis at a concentration of 0.4 mg/ml and 0.8 mg/ml exhibitedcontractility amplitudes of 26.0 mm, 21.5 mm and 27.5 mm and 22.5±1.10 mm, 15.0±1.78 mm and 24.5 ±0.99 mm respectively. The methanol extracts were 25.5±0.70 mm, 23±1.34 mm, 22±1.01 mm and 37.8±1.26 mm, 16.7±2.01 mm, 24.3±0.06 mm respectively, while oxytocin showed 22.8±0.57 mm and 31.0±0.36 mm respectively. The plant leaves were found to have high levels of iron ranging from 2516.587±17.983 (mg/100 g) in B. longipes to 583.317±9.505 (mg/100 g) in V. amygdalina. Rhus natalensis and V. amygdalina had low levels of Zinc. Anti-nutritive phytocompounds such as saponins and Tannins were also detected in some of the test extracts. The study concludes that plants used by pregnant women may have either a positive or negative effect on expectant mothers. There is need to formulate evidence based effective medicines for their safe use in the management of malaria.
Keywords: Medicinal plants; Malaria; Pregnant women; Uterine contractility; Micro-elements; Antinutritive phytocompounds